Analisis Busana Mahasiswa Muslim; Antara Trend dan Syariat - Annisa Fitri; Hapni Laila Siregar; Ahmad Naufal Habibi Lubis; Aulia Eka Putri; Nabilah Asy-Syifa; Siti Wulandari (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
Muslim fashion among Medan State University (Unimed) students shows an interesting dynamic between the latest fashion trends and the values of Islamic law. This research aims to analyze Unimed students' Muslim clothing within the framework of trends and sharia on campus and outside campus. This reseaarch uses quantitative methodes. The analysis technique used is Descriptive Analysis. In this research, descriptive analysis was used to find out how to explain and explain the analysis of UNIMED Student Muslim Clothing, Trends and Sharia. The results of the analysis show that the Muslim clothing worn by Unimed students shows significant variations. Some students tend to follow Muslim fashion trends that are currently popular among teenagers, using bright colors and modern motifs.